Suppression of seed-borne Alternaria arborescens and growth enhancement of wheat with biorational fungicides - Perelló, Analía Edith (2017)
Alternaria spp. are among the major fungal contaminants of wheat grain under postharvest and storage conditions, where A. arborescens was recently detected as a new member of this complex in Argentina causing black point. The aim of this study was to assess the potential of some biorational agents to control A. arborescens and their plant growth promoting of wheat. Seed treatments with spore suspensions of Trichoderma harzianum and Eppicoccum nigrum, extracts from Lippia alba and garlic, sodium bicarbonate, salicylic acid (SA), potassium chloride and dibasic sodium phosphate (SP) were applied to grains of wheat cultivar BIOINTA 1004 before their inoculation with the pathogen. After 7 days, seed germination and infection, necrotic symptoms on emerged seedlings and fresh weight were evaluated. Remarkable results were obtained with L. alba, SA and SP treatments that reduced symptoms markedly compared with the control. Interestingly, necrosis of radicles was significantly reduced by the application of all treatments tested. Moreover, fresh weight of seedlings was significantly increased with the application of the two antagonists, diluted garlic juice and the three tested salts in comparison with controls. Therefore, a positive role as growth promoters can be elucidated. It is concluded that compounds here tested have potential as ecofriendly alternatives to control seed-borne Alternaria fungi of wheat.